Studi Tentang Sertifikasi Guru dalam Meningkatkan Semangat Kerja Dan Kesejahteraan Guru di Kota Samarinda - Joko Herlambang; I Ketut Gunawan; Melati Dama (Jurnal Ilmu Pemerintahan, 2022)
This study aims to describe and analyze the development of the implementation of teacher certification in the city of Samarinda, the phenomena that occur in the implementation of certification and the differences between teacher certification in private and public schools in Samarinda City and more specifically the implications of teacher certification in increasing morale and welfare of teachers in the city of Samarinda. This type of research is descriptive qualitative. Data collection techniques were carried out by means of library research and field research. By using the method of observation, interviews and documentation. Based on the results of the research conducted, it can be concluded that the implementation of teacher certification in the city of Samarinda has increased where initially it was only collecting portfolios, changing to through tests and training in terms of the tests themselves having a high level of difficulty and in terms of training having increasing and solid standards. Phenomena that occur in the implementation of teacher certification are quite diverse, ranging from late payments, test results that are not notified to test takers to senior teachers who have not received certification even though they have taken the test many times. The difference in certification between private and public schools is the amount received, where teachers in private schools receive a nominal value of IDR 1,500,000 and teachers in public schools receive a nominal amount equal to their basic salary.